2023
DOI: 10.1101/2023.01.31.526450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the radiative, thermal and chemical microenvironment of 3D scanned corals

Abstract: 1: Reef building corals are efficient biological collectors of solar radiation and consist of a thin stratified tissue layer spread over a light scattering calcium carbonate skeleton surface that together construct complex three dimensional (3D) colony structures forming the foundation of coral reefs. They exhibit a vast diversity of structural forms to maximize photosynthesis of their dinoflagellate endosymbionts (Symbiodiniaceae), while simultaneously minimizing photodamage. The symbiosis takes place in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
2
1
Order By: Relevance
“…Therefore, S-shaped profiles are expected to occur in a range of species as observed herein. The influence of cilia activity on surface conditions has been observed to be greatest with flow velocities below 1 cm s -1 because faster flow tends to erase the vortices created by beating cilia and the resulting profile structure (Shapiro et al 2014;Murthy et al 2023). While this explains the prevalence of diffusive profiles in our study, S-shaped profiles were more abundant under both flow conditions here than expected based on previous conceptual models (Shapiro et al 2014).…”
Section: Cbl Profile Types Across Species and Water Flow Conditionscontrasting
confidence: 54%
See 1 more Smart Citation
“…Therefore, S-shaped profiles are expected to occur in a range of species as observed herein. The influence of cilia activity on surface conditions has been observed to be greatest with flow velocities below 1 cm s -1 because faster flow tends to erase the vortices created by beating cilia and the resulting profile structure (Shapiro et al 2014;Murthy et al 2023). While this explains the prevalence of diffusive profiles in our study, S-shaped profiles were more abundant under both flow conditions here than expected based on previous conceptual models (Shapiro et al 2014).…”
Section: Cbl Profile Types Across Species and Water Flow Conditionscontrasting
confidence: 54%
“…In our study, CBL was measured above the coenosarc, where it is generally thinner but also more stable than in other areas of the coral because polyp behaviour is less likely to disrupt it. In addition, we performed all measurements on the upstream side of coral fragments, which has a thinner CBL than the downstream side (Edmunds 2005;Murthy et al 2023). Finally, CBL thickness displayed similar patterns in light and darkness across species, demonstrating the overall stability of this trait with variable light conditions.…”
Section: Cbl Traits Differ Between Speciesmentioning
confidence: 99%
“…Studies have shown that in vivo light exposure of symbionts is modulated on a holobiont level to enhance photosynthesis, including alleviating photodamage and bleaching (Lesser and Farrell, 2004;Enriquez et al, 2005;Marcelino et al, 2013;Wangpraseurt et al, 2017), altering inter-and intracellular pH (e.g., Kühl et al, 1995;Gibbin et al, 2014), and directly affecting holobiont temperature (Jimenez et al, 2008(Jimenez et al, , 2012Lyndby et al, 2019). Recently, these experimental insights were integrated in a first multiphysics model of radiative, heat and mass transfer in corals, simulating how coral tissue structure and composition can modulate the internal light, O 2 and temperature microenvironment of corals (Taylor Parkins et al, 2021;Murthy et al 2023). Given a similar global distribution and a benthic lifestyle relying on host-symbiont metabolic interactions, it is feasible to assume that Cassiopea exhibit similar traits, but few studies have investigated to what extent Cassiopea modulate their physicochemical microenvironment (Klein et al, 2017;Arossa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%